El Salvador : Building on Strengths for a New Generation - Calvo-Gonzalez, Oscar (World Bank, Washington, DC, 2015)
Since the end of the Civil War in 1992, El Salvador has advanced on both the social and political fronts. Despite this progress and the recent reductions in income inequality, poverty remains high, largely as a result of low economic growth. This Systematic Country Diagnostic argues that the challenge in El Salvador is not to identify the proximate constraints to growth, but how those constraints are inter-connected and what entry points may help break what can be characterized as "vicious circles." The Systematic Country Diagnostic identifies three inter- connected vicious circles that hamper growth and shared prosperity: (1) a cycle of low growth and violence; (2) a cycle of low growth and migration; and (3) a cycle of low growth, savings and investment. Moreover, it also notes action on the identified entry points will require a "big push" (rather than marginal interventions) that help break the existing development dynamics. But this Systematic Country Diagnostic also identifies some strengths that El Salvador could build on to propel growth. Areas of opportunity include migration with the positive impact of diaspora on development, geographic and cultural proximity to large export markets, particularly the U.S., and an industrial base that can support an expansion of the tradable sector. At 20 percent of GDP the manufacturing sector is large by Latina American and by middle-income country standards.